Lithium occurrence and coal facies control of Longtan formation in Northern Guizhou, China - Xiwei, Mu; Yu, Song; Meng, Wang; Guangjun, Feng; Peiming, Zhou (Frontiers in Earth Science, 2025)
Coal seams have been recognized as a promising geological reservoir for lithium, and its enrichment is intimately correlated with the original coal-forming parent materials and sedimentary microfacies. Nevertheless, the influence of coal facies on lithium enrichment has hitherto been scarcely documented. In this research endeavor, with the aim of unraveling the effects of coal facies on the lithium enrichment within coal measure strata, a combination of optical microscope examination, the step-by-step chemical extraction (SCEP) technique, inductively coupled plasma mass spectrometry (ICPMS), and scanning electron microscopy (SEM) was utilized to probe into the occurrence of lithium and the control exerted by coal facies in the Longtan Formation of northern Guizhou. The findings revealed that the coal-forming environment of the Longtan Formation was a humid forest swamp with low-living-water and hydrodynamic conditions, which consequently augmented the salinity and reducibility of the sedimentary microfacies. The Sr/Ba ratios in the Longtan Formation fluctuated from 0.40 to 3.39, averaging 1.63, signifying a marine sedimentary milieu. The SCEP outcomes indicated that lithium in the Longtan Formation was predominantly in the silicate-bound form, constituting 71.67%–93.14% (with an average of 87.32%), wherein clay minerals served as the principal carriers of lithium within the coal. A positive correlation was observed between the tissue preservation index and the lithium content (R2 = 0.82), implying that the lithium content in the coals of the Longtan Formation was closely tied to the enrichment of structured plant tissues during the peat swamp accumulation stage. The lithium content primarily exhibited an upward trend with the intensification of the groundwater influence (GWI), suggesting that more vigorous groundwater dynamic conditions could result in a higher lithium content in coal. In comparison to previous investigations, this study represents an advancement by elucidating the enrichment environments of lithium in coal through the comprehensive cross-analysis of both the coal-forming parent materials and sedimentary microfacies. The results hold substantial significance for comprehending the occurrence mechanism and exploration engineering of lithium in coals.